2017
DOI: 10.1186/s12870-017-1093-4
|View full text |Cite
|
Sign up to set email alerts
|

The core regulatory network of the abscisic acid pathway in banana: genome-wide identification and expression analyses during development, ripening, and abiotic stress

Abstract: BackgroundAbscisic acid (ABA) signaling plays a crucial role in developmental and environmental adaptation processes of plants. However, the PYL-PP2C-SnRK2 families that function as the core components of ABA signaling are not well understood in banana.ResultsIn the present study, 24 PYL, 87 PP2C, and 11 SnRK2 genes were identified from banana, which was further supported by evolutionary relationships, conserved motif and gene structure analyses. The comprehensive transcriptomic analyses showed that banana PYL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 62 publications
2
23
1
Order By: Relevance
“…The suppressed expression of SlMBP8 , a MADS-box gene, promotes carotenoid and ETH biosynthesis and induces the expressions of cell wall metabolism genes, which ultimately accelerate tomato fruit ripening ( Yin et al, 2017 ). The MADS-box genes of MaMADS24 and MaMADS49 regulate the fruit development and ripening process by interacting with MaMADS proteins themselves and ETH signal transduction, biosynthesis-related proteins, starch biosynthesis proteins, and metabolism-related proteins ( Liu et al, 2013 ; Hu et al, 2017 ). The PrupeSEP1 gene, a subfamily of MADS-box transcription factors, regulates fruit ripening and softening by exhibiting similar expression patterns of cell wall modification-related genes and N-glycan processing genes in melting flesh peach ( Li et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suppressed expression of SlMBP8 , a MADS-box gene, promotes carotenoid and ETH biosynthesis and induces the expressions of cell wall metabolism genes, which ultimately accelerate tomato fruit ripening ( Yin et al, 2017 ). The MADS-box genes of MaMADS24 and MaMADS49 regulate the fruit development and ripening process by interacting with MaMADS proteins themselves and ETH signal transduction, biosynthesis-related proteins, starch biosynthesis proteins, and metabolism-related proteins ( Liu et al, 2013 ; Hu et al, 2017 ). The PrupeSEP1 gene, a subfamily of MADS-box transcription factors, regulates fruit ripening and softening by exhibiting similar expression patterns of cell wall modification-related genes and N-glycan processing genes in melting flesh peach ( Li et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…The functions of the ubiquitin mediated proteolysis pathway in the regulation of fruit ripening have been studied in banana, tomato, papaya, and barbarum, and these studies confirm the regulatory role of the ubiquitin proteasome in the fruit ripening process ( Liu et al, 2013 ; Wang et al, 2014 ; Bi et al, 2015 ; Zeng et al, 2015 ). Research on the regulatory mechanism of fruit ripening indicates that MADS-box transcription factors have a pivotal effect on fruit ripening by regulating carotenoid synthesis, the ETH signaling pathway, cell wall metabolism, flavonoid and lignin biosynthesis, and cuticle development in apple, banana, tomato, and peach ( Youssef et al, 2012 ; Ireland et al, 2013 ; Liu et al, 2013 ; Feng et al, 2016 ; Garceau, Batson & Pan, 2017 ; Yin et al, 2017 ; Hu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, a few genetic studies mainly on MAPK cascades-ICE1-CBF pathway and ABA signaling have been reported. Recently, comprehensive transcriptomic analyses have shown that banana PYL-PP2C-SnRK2 genes, the core components of ABA signaling, are involved in response to cold stress ( Hu et al, 2017b ) and MaMEKK1-MaMKK2 genes are activated by cold stress in cold-resistant banana ( Wang et al, 2017 ). The rapid activation and selective induction of ICE1 and MYBS3 cold tolerance pathways in Dajiao may be one of the main reasons that Dajiao has higher cold resistance than Cavendish ( Yang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Highthroughput next generation sequencing showed that PYL, PP2C, and SRK2E respond to drought stress in Gossypium spp [53]. In banana, the PYL-PP2C-SnRK2 gene family regulated its tolerance to abiotic stress, such as salt and drought stress conditions [54]. In this work, transcriptome data from C. sinensis treated with PEG and NaCl were obtained from the NCBI-SRA database and analyzed.…”
Section: Discussionmentioning
confidence: 99%